2017
DOI: 10.1155/2017/5787854
|View full text |Cite
|
Sign up to set email alerts
|

Patient–Physician Differences in Desired Characteristics of NSAID Plasters: An Online Survey

Abstract: In Japan, adhesive skin plasters containing nonsteroidal anti-inflammatory drugs (NSAIDs) are frequently used to treat pain of musculoskeletal origin. There are many reports on their efficacy but few on patients' impressions of usability or levels of satisfaction. Objectives. To elucidate the differences in perception between patients and physicians concerning NSAID plasters. Subjects. We conducted two surveys about NSAID plasters on patients and physicians. 600 patients currently using plasters and 200 physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…The Cohen's kappa coefficient was 0.7937 in the first phase of the selection process (screening of both titles and abstracts) and 0.9217 in the second phase (full-text readings). The reasons for excluding 24 studies that were fully read were as follows: the study was a systematic review without original data (n = 3) [19][20][21] ; the study did not consider the preferences of patients (n = 4) 13,14,22,23 ; the study analyzed preferences but not for treatment characteristics (n = 11) [24][25][26][27][28][29][30][31][32][33][34] ; the pain site was somewhere other than in the low back or data were aggregated with other sites (n = 4) [35][36][37][38] ; the study was a sub-study of another one (n = 1) 39 ; and data was not available even after contacting the authors (n = 1) 40 . Details of the process selection can be found in the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) flow diagram in Figure. Table 1 lists the 13 selected studies.…”
Section: Resultsmentioning
confidence: 99%
“…The Cohen's kappa coefficient was 0.7937 in the first phase of the selection process (screening of both titles and abstracts) and 0.9217 in the second phase (full-text readings). The reasons for excluding 24 studies that were fully read were as follows: the study was a systematic review without original data (n = 3) [19][20][21] ; the study did not consider the preferences of patients (n = 4) 13,14,22,23 ; the study analyzed preferences but not for treatment characteristics (n = 11) [24][25][26][27][28][29][30][31][32][33][34] ; the pain site was somewhere other than in the low back or data were aggregated with other sites (n = 4) [35][36][37][38] ; the study was a sub-study of another one (n = 1) 39 ; and data was not available even after contacting the authors (n = 1) 40 . Details of the process selection can be found in the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) flow diagram in Figure. Table 1 lists the 13 selected studies.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, switching from oral to patch NSAIDs in high‐risk patients is not expected to offer any additional advantage in lowering the risk of developing these events. Moreover, as shown in an online survey in Japan, 37% of patients used patch NSAIDs along with oral NSAIDs owing to dissatisfaction with patches alone 43 44 …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as shown in an online survey in Japan, 37% of patients used patch NSAIDs along with oral NSAIDs owing to dissatisfaction with patches alone. 43 Therefore, when pain is not relieved by NSAIDs, switching to other treatments should be considered. 44 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…66 In another Japanese study evaluating patients' desired characteristics of NSAID topical plasters, analgesic efficacy, including analgesic strength, length of action, and early onset of action, followed by avoiding skin irritation and low medication cost were the characteristics most frequently reported as desirable by patients. 67 Studies have found that increasing patients' knowledge through education about the causes of knee pain, treatment mode of action, and adverse effects improves both adherence and informed choice. 68,69 It is therefore important for healthcare professionals to engage patients in a shared decision-making process to encourage the use of topical NSAIDs among suitable patients and to promote treatment adherence.…”
Section: Grade Of Recommendation: Amentioning
confidence: 99%